URBAN FORM AND TRANSPORTATION ENERGY CONSUMPTION IN DEPOK CITY - Widya Putri, Devina
By combining transportation energy use per capita for main, side, and weekend activities, this research attempts to explore the correlation between transportation energy consumption and urban form in village scale. Studies about the influence of urban form towards the amount of energy consumption in transportation sector have been done several times in many cities in the world and have shown that urban form variables, both related with built environment, such as density, diversity, and design, and network, such as distance to CBD, distance to public transportation, connectivity, and accessibility, effect how much of energy the people use for mobility. Conducted in Depok, a satellite city in Jabodetabek metropolitan area (JMA), Indonesia, four different urban form variables were measured, including the population density, the land use mix, the street connectivity, and the public transportation range area. Other four traveller characterstics variables, consisted of household size, private vehicle ownership, driving license ownership, job type, and monthly income were also observed in the process. Urban form and traveller characteristics variables acted as the independent variable, while transportation energy consumption variable as the dependent one. This research used quantitative approach and the data on present individual energy consumption in transportation sector was acquired through online questionnaire. The results of descriptive analysis, association analysis and one-way analysis of variance show three findings in relation to transportation energy consumption in Depok city. Firstly, the population density and the street connectivity are proven to be correlated with the amount of transportation energy consumed. Secondly, middle urban form compactness level outweighs the high level in terms of energy consumption for travelling routine per capita per week. Lastly, difference in private vehicle ownership, driving license ownership, and job type results in different transportation energy usage. According to those findings, this research recommends Depok city government to intervene in increasing density and connectivity attribute in village administration scale, as well as to tighten the rules about private vehicle and driving license ownership, in order to decrease the transportation energy consumption in Depok city